Inhibition of Arachidonic Acid Release by Cytosolic Phospholipase A2 Is Involved in the Antiapoptotic Effect of FK506 and Cyclosporin A on Astrocytes Exposed to Simulated Ischemia In Vitro - Bozena Gabryel; Malgorzata Chalimoniuk; Anna Stolecka; Katarzyna Waniek; Jozef Langfort; Andrzej Malecki (Elsevier, 2006)
In the present study, we investigated whether the protective effect of FK506 and cyclosporin A (CsA) against in vitro ischemic injury of astrocytes might be mediated through attenuation of cytosolic isoform of phospholipase A2 (cPLA2) expression and activity as well as inhibition of arachidonic acid (AA) release. On the 21st day in vitro, cultures of rat astrocytes were subjected to ischemia-simulating conditions (combined oxygen glucose deprivation) for 8 h and exposed to FK506 (10 - 1000 nM) and CsA (0.25 - 10 µM). Obtained data suggest the crosstalk between the action of 0.25 - 10 µM CsA as well as 1 µM FK506 on calcineurin (CaN) and cPLA2 in anti-apoptotic signal transduction pathways. Moreover, we have shown that immunosuppressants at these concentrations protected glial cells against ischemia-induced apoptosis through the increase of cell viability, mitochondrial function restoration, and attenuation of oxidative stress. Finally, in our study, low concentrations of FK506 (10 and 100 nM) exerted limited effects on the assessed parameters. Our findings document a key role either for CaN or cPLA2 expression attenuation and AA release inhibition in the antiapoptotic effect of FK506 and CsA in ischemic astrocytes. Keywords:: FK506, cyclosporin A, astrocyte, apoptosis, cytosolic phospholipase A2